Functions and mechanics of dynein motor proteins - Roberts, Anthony J. (2013)
Fuelled by ATP hydrolysis, dyneins generate force and movement on microtubules in a wealth of biological processes, including ciliary beating, cell division and intracellular transport. The large mass and complexity of dynein motors have made elucidating their mechanisms a sizable task. Yet, through a combination of approaches, including X-ray crystallography, cryo-electron microscopy, single-molecule assays and biochemical experiments, important progress has been made towards understanding how these giant motor proteins work. From these studies, a model for the mechanochemical cycle of dynein is emerging, in which nucleotide-driven flexing motions within the AAA+ ring of dynein alter the affinity of its microtubule-binding stalk and reshape its mechanical element to generate movement.